Early Life Exposure to Adverse Childhood Experiences and School Readiness Among Preschoolers with Disruptive Behaviors. - Gutierrez, Akira S.; Zambrana, Katherine; Poznanski, Bridget; Valdes, Jorge; Hart, Katie C. (Journal of Child & Family Studies, 2024)
This study explored the associations between Adverse Childhood Experiences (ACEs) and functioning across several school readiness domains among preschoolers with disruptive behavior problems. The sample included 115 children (M= 5.18, 67.8% male; 32.2% female) from a large, urban, high-poverty community, with predominantly Black families, who were about to enroll in a summer treatment program prior to kindergarten. As part of pre-treatment assessments, caregivers completed interviews and questionnaires about adverse experiences and stressors in their children's lives. Children's behavioral, academic, and social functioning were also assessed at this time. We identified exposure to ACEs using multimodal parent reports. A path analysis was conducted between preschoolers' exposures to ACEs and their school readiness, covarying outcomes with one another to isolate the effect of ACEs. Our findings indicate a dose-effect, such that exposure to a higher number of ACEs is significantly associated with more severe disruptive behaviors, internalizing problems, and global impairment in the child's functioning. However, there were no significant associations between total number of ACEs and academic or social functioning. Notably, the prevalence of ACEs among this sample of preschoolers living in highly under-resourced communities was strikingly higher than national samples, with 93.9% of parents reporting exposure to at least one ACE by age 5, compared to 19–26% in a nationally samples; moreover, 62.6% experienced 3 or more ACEs, compared to 5.35% in same-aged samples (Briggs-Gowan et al., 2010; Jackson et al., 2021). Our study contributes to the growing literature on the importance of recognizing the heightened risk of early and compounding adversity in school readiness outcomes for young children with special needs. Implications for early intervention timing and the need to consider readiness for preschool are discussed. Study Highlights: We investigate associations between adversity and school readiness in preschoolers with disruptive behaviors living in a low income community. We identify exposure to ACEs using multimodal parent report from clinical interviews and surveys. We find that 94% of participants had experienced at least 1 ACE and 49% had experienced 4 or more. We find a dose effect between number of ACEs and severity of disruptive and internalizing problems, and global impairment.